2018
DOI: 10.1016/j.msard.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on cytokines and adipokines in multiple Sclerosis: A systematic review

Abstract: Research regarding the effects of exercise training on cytokines and adipokines in MS is in its infancy, but exercise represents an adjuvant therapy in MS, and future studies are essential for clarifying the role of exercise on cytokines and adipokines in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 62 publications
6
43
2
Order By: Relevance
“…Based on the PEDro scale, this study had the highest methodological quality (9/10). However, this study did not satisfy the fifth PEDro criterion (blinding all subjects); this criterion is not applicable for exercise training intervention studies . Other research confirms that resting serum levels of MMP‐9 remain stable after combined training; however, this study had >15% drop‐out of participants, which undermined the results.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Based on the PEDro scale, this study had the highest methodological quality (9/10). However, this study did not satisfy the fifth PEDro criterion (blinding all subjects); this criterion is not applicable for exercise training intervention studies . Other research confirms that resting serum levels of MMP‐9 remain stable after combined training; however, this study had >15% drop‐out of participants, which undermined the results.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, brain volume showed a trend, which was not significant, towards a reduced rate of brain atrophy during supervised exercise training. Our recent systematic review concluded that exercise training (i.e. resistance training) can reduce pro‐inflammatory cytokine levels, which can lead to reduced brain atrophy and lesion development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of human studies look primarily at the peripheral effects of exercise in MS patients including serum and plasma cytokine concentrations (reviewed in Heesen, Romberg, Gold, & Schulz, 2006;Negaresh et al, 2018). There is evidence that exercise can reduce the permeability of the blood-brain barrier (BBB) which would indicate that exercise may result in exclusion of immune cells from the CNS (Schön et al, 2019;Souza et al, 2017).…”
Section: Human Studies Of Cns Neuroinflammationmentioning
confidence: 99%
“…The controlling of mass and phenotype fatty tissue is an effective approach to regulate adipokines and their underlying pathways (Figure 1). Our recent review observed that research regarding the effects of exercise training on adipokines and cytokines in pwMS is in its infancy (51). We are aware of only three original investigations that studied the effects of exercise intervention on adipokines in pwMS.…”
Section: Immune and Adipokine Markersmentioning
confidence: 99%